2017
DOI: 10.1007/5584_2016_181
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Influenza Diagnostic Tests Improve Suitability of Antiviral Treatment in Hospitalized Children

Abstract: Influenza may have a complicated course in young children. The aim of the study was to analyze the suitability of influenza treatment among children younger than 5 years hospitalized due to an influenza-like illness. We conducted a comparison of the treatment among children hospitalized in two consecutive years: 2015, when no rapid influenza diagnostic tests (RIDT) were in use, and 2016, when RIDT were implemented into a routine practice in the pediatric ward. In both seasons, nasopharyngeal swabs were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…described similar findings among discharged patients with ILI who were tested with RIDT 13 . Similar findings were also described by Nitsch‐Osuch et al 19 . In contrast, among discharged patients in our study, RIDT (regardless of location) was not associated with less antibiotics prescriptions.…”
Section: Discussionsupporting
confidence: 92%
“…described similar findings among discharged patients with ILI who were tested with RIDT 13 . Similar findings were also described by Nitsch‐Osuch et al 19 . In contrast, among discharged patients in our study, RIDT (regardless of location) was not associated with less antibiotics prescriptions.…”
Section: Discussionsupporting
confidence: 92%
“…A recent randomised controlled trial by Brendish et al found significantly higher prescription rates (91% vs 65%, P = 0.0026) amongst study groups diagnosed by POCT. Another recent study by Nitsch‐Osuch et al of preimplementation and postimplementation of POCTs showed increased antiviral use in post‐POCT patients (64% vs 0%, P < 0.05). Likewise, Li‐Kim‐Moy et al (46.2% vs 21.5%, P = 0.001); Blaschke et al (56% vs 19%, P = 0.002); and Jennings et al (60.1% vs 24.6%, 4618/7658 vs 178/725) all reported that influenza positive patients had significantly increased antiviral use amongst those diagnosed by a POCT compared with standard testing.…”
Section: Resultsmentioning
confidence: 89%
“…Twenty‐six studies assessed the effect of POCT on antibiotic prescription rates (Table ). Eleven (42.3%) of these papers compared POCT with standard testing and reported significant decreases in antibiotic use in patients receiving an influenza positive POCT diagnosis. In addition to comparing POCT and standard testing, three of the studies also assessed differences between positive and negative POCT results, demonstrating that patients positive for influenza by POCT were significantly less likely to receive antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…it has been shown that rapid influenza diagnostic tests have a positive effect on clinical decisions by: reducing the number of antibiotics used in patients with influenza-like symptoms, rationalizing the use of anti-influenza drugs (oseltamivir), reducing the number of additional tests ordered, and reducing the duration of stay in the emergency department, and for these reasons riDts should be used, keeping in mind the limitations described above [88][89][90].…”
Section: Rapid Influenza Diagnostic Tests -Immunochromatographic Assaysmentioning
confidence: 99%